Costo- efectividad y costo - utilidad de la capsaicina parche transdérmico al 8% frente a pregabalina, en el tratamiento de pacientes con dolor neuropático periférico en Colombia (2017)
Objective. An economic evaluation was carried out with the purpose of evaluating the cost-effectiveness and cost-utility of Capsaicin at 8% in transdermal patch versus Pregabalin in capsules, in the treatment of peripheral neuropathic pain in Colombia. Methodology. A decision tree was modeled to evaluate the cost-effectiveness and cost-utility of the proposed health alternatives, contemplating a hypothetical cohort of 100 patients and a time horizon of 2 years. Results. By modeling the decision tree, cost-effectiveness (pain reduction in a value ≥30% in a period of two months) and cost-utility (QALY) in the treatment of peripheral neuropathic pain in Colombia was evaluated. . It is evidenced that 8% capsaicin in transdermal patch is the dominant alternative (65 patients present pain reduction ≥ 30% and 144 QALYs), compared to Pregabalin in capsules (60 patients present pain reduction ≥ 30% and 139 AVAC), obtaining an ICER of -119,434,135. The total costs that must be invested with each intervention is $ 212,604,414 and $ 610,801,989 respectively. In the univariate sensitivity analysis, the ICER remained negative, revealing that capsaicin in the transdermal patch is the dominant option compared to Pregabalin. Conclusion. After evaluating the parameters of cost effectiveness and utility cost by modeling the decision tree, it is evident that capsaicin is the dominant alternative to Pregabalin, generating lower costs and greater health benefits, being cost effective and therefore, recommends its use and implementation to treat patients suffering from peripheral neuropathic pain in Colombia.